Spinel-functionalized bamboo-derived hierarchical carbon: dual activation strategy for synergistic double-layer/pseudocapacitance energy conversion - Jin, Luanxing; Cheng, Zhi; Zhang, Shuhan (Frontiers in Materials, 2025)
To overcome the dual bottlenecks of low intrinsic energy density in carbon materials and poor cycling stability of metal oxides, this study proposes a biomimetic hierarchical pore engineering strategy. Bamboo-derived biochar is transformed into a hierarchically porous architecture via synergistically coupled CO₂ physical activation (PHAC) and KOH chemical activation (CHAC), yielding ultra-micropores (0.55 nm, 42%) and mesopores (1.32 nm, 38%) with a micropore/mesopore volume ratio of 0.45. Ultrasonic-assisted impregnation enables uniform anchoring of 5 wt% MnCo₂O₄ spinel, forming strong interfacial C-O-Mn/Co bonds (12.4%) and mixed Mn³⁺/Mn²⁺ (62:38) that synergistically enhance charge transfer. The composite electrode achieves exceptional performance: 1258 F/g at 1 A/g, 80% capacity retention at 10 A/g, and 59.18 Wh/kg at 8.42 kW/kg. Critically, the dual activation eliminates negative pore volume artifacts and accelerates H⁺ transport in PEMFC hierarchical pores, establishing a new paradigm for hybrid energy storage.